Processing conditions affecting residual stresses and fatigue properties of cold spray deposits. Issue 9 (December 2015) - Cavaliere, P.; Silvello, A.
Abstract Cold spraying is an innovative coating technology mainly based on the high-speed impact of metallic particles on different substrates. Through the employment of low-temperature gases (air, He, N2 ), spray particles (usually 1–50 μm in diameter) are accelerated to a high velocity (typically 300–1200 m/s) that is generated through a convergent-divergent de-Laval-type nozzle. Severe plastic deformation of particles impacting on the substrate occurs at temperature well below the melting point leading to the unique mechanical properties experienced by such kinds of coatings. In the present paper, the main processing parameters affecting the fatigue behavior of metal-metal cold spray deposits are described. In the present paper, the effect of processing parameters on fatigue properties were analyzed for different materials such as AA7075 sprayed on AA7075 substrate, AA2024 sprayed on AA7075 substrate, and AA2024 sprayed on AZ91 magnesium alloy substrate. Many experimental conditions have been analyzed in terms of particle dimensions and composition, substrate temperature and composition, gas temperature and pressure, and nozzle properties. In particular, they were analyzed those conditions leading to an increase in fatigue life.